Bone Cutting Forceps: A Safe Approach for Saving Strangulated Penis - Mohamed Ahmed Abd El Salam; Ahmed Gamal; Hossam Elenany (Case Reports in Medicine)
Penile strangulation is considered a rare andrological emergency that may lead to a wide range of complications. Penile strangulation may be related to mental retardation in children or hypersexuality, abnormal sexual preferences in adults. This case report shows a 23-year-old male who presented to the emergency room with agonizing pain related to a metallic ring placed at the base of the penis for more than 8 hours during an attempt of masturbation. Removing this metallic ring and saving the patient’s penis from gangrene without causing injury were very challenging. Patient was successfully managed and had an uneventful recovery.